PENDIDIKAN KESEHATAN JIWA PADA TAHAP PERKEMBANGAN ANAK USIA SEKOLAH DI SDN 59 PEKANBARU - Rahmadania, Nazhifah Hawadya (PITIMAS: Journal of Community Engagement in Health, 2025)
School-age children are individuals aged 6–12 years who experience rapid growth in physical, cognitive, emotional, social, and moral aspects. At this stage, children begin adapting to the school environment and developing independence and responsibility. This health education activity aimed to improve the knowledge of fourthgrade students at SDN 59 Pekanbaru regarding school-age developmental readiness. School-age children were chosen as the target group because this stage is a critical periodfor forming learning habits, discipline, and social skills that influence future developmental success.The program was conducted on October 29, 2025, with 27 participants (14 boys and 13 girls). Themethods used included lectures, discussions, and pre- and post-tests to measure students’ understanding. The results showed an increase in the average score from 85.19 (pre-test) to 93.33 (post-test), with all participants achieving a good category. The 8.14-point improvement indicates that the health education was effective in enhancing students’ comprehension and readiness related to school-age development in physical, cognitive, emotional, and social aspects. Therefore, this activity played an important role in fostering students’ awareness of the importance of supporting optimal growth and development during the school-age period.